72-92 Essex Street, ca. 1860 - Unknown (Tufts Archival Research Center, 2005)
Street-level view west of (left to right) 72-92 Essex Street, located between Chauncy Street to the west-southwest and Edinborough Street to the east-northeast. The facades of the houses face south-southeast towards Essex Street. The south-southeast elevation of the Rowe Street Baptist Church, located on the northeast corner of Chauncy and Essex Streets, is visible near the left side of the photograph. Street lights line the sidewalks. Image is included in Chinatown Banquet exhibit. Image is part of the Henry P. Curtis Collection. 7 1/8 in diameter (image is round), 10 x 7 7/8 overall Photographs